Edukasi Pengelolaan Sampah Untuk Menumbuhkan Kesadaran Diri Sejak Dini di MIN 2 Solok, Jorong Balai Pinang, Nagari Muaro Paneh, Kecamatan Bukit Sundi - Donny Fernandez; Karin Gifa Ananta Sari; Rahmatul Azizah; Arhaya Umil Azmah; Irvan Ramdani; Citra Sri Rahmadani (CV. ITTC INDONESIA, 2025)
Waste problem has become a crucial issue in Indonesia, including in Solok area. This research aims to foster self-awareness of elementary school children regarding waste management through interactive and comprehensive educational activities. This activity is part of the Community Service Program (KKN) carried out at MIN 2 Solok, Jorong Balai Pinang, Nagari Muaro Paneh, Bukit Sundi District, Solok Regency. The method used in this educational activity is a combination of presentations, lectures, and interactive discussions with material including the concept of waste, types of waste, positive and negative impacts of waste, the importance of waste sorting, and evaluation through quiz. The results of the activity show that students have a good interest and understanding of waste management materials, especially in practical aspects such as waste sorting and recycling potential. This activity made a positive contribution in changing students' perception of waste from something that must be avoided to potential that can be developed into valuable products. It is hoped that this education can be the foundation in forming an environmentally conscious generation that is able to implement sustainable waste management.